2014
DOI: 10.1021/ol403517p
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Oxidative Coupling of Enamides and Alkynes for Synthesis of Substituted Pyrroles

Abstract: A novel and efficient palladium(II)-catalyzed alkenyl C-H activation oxidative annulation of enamides with alkynes for the synthesis of substituted pyrroles has been developed. The reaction tolerates a wide range of functional groups and is a reliable method for the synthesis of triaryl-substituted pyrroles in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…Later, Guan and coworkers reported Pd‐catalyzed oxidative coupling of enamides and alkynes for the synthesis of substituted pyrroles (Scheme a). [39a] Similarly, the research groups of Wang and Pawar independently reported oxidative annulations of enamides with alkynes under Ru II and Co III catalysis conditions, respectively (Scheme a). [39b], [39c] They also obtained the synthetically useful N–H pyrroles with use of an identical catalytic system by fine‐tuning the reaction conditions.…”
Section: C–h Functionalization Of Anilidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Guan and coworkers reported Pd‐catalyzed oxidative coupling of enamides and alkynes for the synthesis of substituted pyrroles (Scheme a). [39a] Similarly, the research groups of Wang and Pawar independently reported oxidative annulations of enamides with alkynes under Ru II and Co III catalysis conditions, respectively (Scheme a). [39b], [39c] They also obtained the synthetically useful N–H pyrroles with use of an identical catalytic system by fine‐tuning the reaction conditions.…”
Section: C–h Functionalization Of Anilidesmentioning
confidence: 99%
“…This protocol uses [RhCp*Cl 2 ] 2 as a catalyst and sluggishly reactive aminopyridines as starting materials (Scheme b). [39d] Later, the research group of Glorius reported a unique rhodium(III)‐catalyzed, hydrazine‐directed C–H activation protocol for the synthesis of indoles . This protocol avoids the usage of external oxidant because it employs facile cleavage of the N–N bond as an oxidant.…”
Section: C–h Functionalization Of Anilidesmentioning
confidence: 99%
“…In 2014, Guan et al [39] reported the synthesis of pyrroles through oxidative annulation of enamides with alkynes employing Pd(OAc) 2 and Xantphos as the catalyst and ligand, respectively (Scheme 30). The transformation showed high functional group tolerance towards both sides.…”
Section: Scheme 28mentioning
confidence: 99%
“…52 The efficiency of this oxidative coupling was greatly improved in the presence of a biphosphine ligand, in particular Xantphos. The DHA also proceeded with aliphatic alkynes, methyl phenyl alkyne leading to the two regioisomers.…”
Section: Via Enamide-alkyne Couplingmentioning
confidence: 99%